2011
DOI: 10.1128/aac.01433-10
|View full text |Cite
|
Sign up to set email alerts
|

Protein Binding: Do We Ever Learn?

Abstract: 6Although the influence of protein binding (PB) on antibacterial activity has been reported for many antibiotics and over many years, there is currently no standardization for pharmacodynamic models that account for the impact of protein binding of antimicrobial agents in vitro. This might explain the somewhat contradictory results obtained from different studies. Simple in vitro models which compare the MIC obtained in protein-free standard medium versus a protein-rich medium are prone to methodological pitfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
196
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(207 citation statements)
references
References 107 publications
7
196
1
3
Order By: Relevance
“…Note that the IC 50 values are taken from in vitro analysis and protein-binding in an in vivo setting might influence these values (Zeitlinger et al, 2011). Therefore, we found that when considering different drugs to use for IP chemotherapy, not only transport parameters, but also biological parameters like IC 50 values and protein binding should be taken into account.…”
Section: Resultsmentioning
confidence: 99%
“…Note that the IC 50 values are taken from in vitro analysis and protein-binding in an in vivo setting might influence these values (Zeitlinger et al, 2011). Therefore, we found that when considering different drugs to use for IP chemotherapy, not only transport parameters, but also biological parameters like IC 50 values and protein binding should be taken into account.…”
Section: Resultsmentioning
confidence: 99%
“…Such differences really matter, as the free fraction used as basis for PK/PD calculations could be assumed to be as low as 30% and 48% or as high as 60% and 75%, respectively. These differences are very likely due to methodological differences as reviewed previously [3,59], but the question is which of the published data should be selected for PK/PD calculations and based on which criteria?…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic in vivo efficacy of antibacterials, however, is the complex result of a number of factors. On the one hand, protein binding has a strong impact on minimal inhibitory concentrations (MICs) of antibacterials for the pathogen to be treated as well as on pharmacokinetics (PK) and pharmacodynamics (PD) of the agent as the free fraction only crosses pro-as well as eukaryotic membranes thus reaching intracellular targets or distributing between the intra-and extravascular spaces; furthermore, protein binding can alter renal excretion, half-life and volume of distribution thus affecting PK/PD-surrogates [1][2][3][4][5]. On the other hand, serum proteins protect the host from serious sequelae of an infection and/or may increase antibacterial activities.…”
Section: Introductionmentioning
confidence: 99%
“…However this increase is in opposite direction which is normally described in the literature. 4,18 The presence of a competitive protein binder at lower concentrations, or multiple binding sites with different affinities could explain the observed trend.…”
Section: Flutamide-albumin Binding Studymentioning
confidence: 98%
“…On the other hand analyzing the free fraction of the drug in study samples would be the main issue demanding the sensitive analytical methods. 4 The gas chromatographic determination of flutamide in blood was reported in 1988 by Schulz et al for a limited range of concentration (0.02-0.250 µg/ml). 1 In another study by Manjunath et al, HPLC system was equipped with a radioactive detector and a gradient solvent system was used for radioactive flutamide determination with 18.3 minutes retention time.…”
Section: Introductionmentioning
confidence: 99%